Design and implementation of a 1.65~3 GHz 500 watts power amplifier - Xue Xin; Dong Liang; Wu Jiaqian (Dianzi Jishu Yingyong, 2022)
Modern transmission systems have put forward higher and higher requirements for the working frequency band and power level of power amplifiers, and the design of power amplifiers based on GaN power devices can meet these new requirements. In this paper, GaN HEMT is used to design the basic power amplifier unit, and the 5-path power synthesizer with asymmetric structure is innovatively used to realize the required power of the whole machine and improve the efficiency of the whole machine. The operating frequency of the power amplifier is 1.65~3 GHz, the measured output power is greater than 500 W(CW), and the power conversion efficiency is greater than 25%. Compared with similar products, the efficiency and volume index have been greatly improved.This product is suitable for high-power system applications, such as EMC testing, electronic countermeasures, etc.